2020
DOI: 10.1007/s10903-020-01056-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status, Oral Health Behaviours and Oral Health Care Utilisation Among Migrants Residing in Europe: A Systematic Review

Abstract: As the reported data on oral health status among the migrants in Europe is fragmented, we systematically reviewed the published literature on the oral health status, behaviours and care utilisation among migrants residing in Europe. For this, we retrieved publications from PubMed and EMBASE, supplemented by manual citation screening and grey literature search on Google scholars. Two independent reviewers screened the studies, extracted data and critically appraised the publications. A total of 69 studies inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 28 publications
(45 reference statements)
3
24
0
Order By: Relevance
“…Nevertheless, the evidence is less explicit for older immigrant adolescents, as discrepancies were observed regarding caries experience levels across different European countries. Some studies demonstrated dental health among certain immigrant sub-groups approximating or even being superior to that of native residents, in contrast to other reports in which adolescents with an immigrant background presented with an inferior dental status to their host peers [ 5 ].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Nevertheless, the evidence is less explicit for older immigrant adolescents, as discrepancies were observed regarding caries experience levels across different European countries. Some studies demonstrated dental health among certain immigrant sub-groups approximating or even being superior to that of native residents, in contrast to other reports in which adolescents with an immigrant background presented with an inferior dental status to their host peers [ 5 ].…”
Section: Introductionmentioning
confidence: 81%
“…As has been mentioned, the majority of ‘settled’ immigrants in Greece originate from Eastern European countries, most frequently from Albania. Epidemiological evidence from studies conducted in Western European countries suggests that, among adults, adolescents and children with an immigrant background, those with Eastern European origin present a higher dental caries prevalence [ 5 , 23 , 24 , 25 , 26 , 27 ]. Moreover, native Eastern European children and adolescents present with considerably higher caries levels compared with their Western European peers [ 11 ], an observation that is possibly associated with the privatisation and decentralisation of the oral healthcare delivery system in these territories during the last three decades, which has impeded the provision of dental care services in childhood populations, leading to detrimental effects on disease levels [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of a poorer oral health among migrants compared to the host population has been demonstrated in the literature [15,16], even though information about this topic remains contradictory. Studies from Germany and Spain, included in the systematic review by Pabbla et al [17], reported higher dental caries experience (DMFT Index) in migrants adolescents compared to the host population, but, on the contrary, re-searchers performed in United Kingdom (UK), Denmark and Sweden showed a lower DMFT Index among non-native subjects compared to the native population. Al-merich-Silla et al demonstrated that immigration status and social class were significantly associated with higher caries level in immigrant children compared to Spanish children of the Valencia region [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research, it was found that there was a significant relationship between the work of the head of the family and the DMFT index [9,10] . Work is related to the level of income or level of expenditure.…”
Section: Introductionmentioning
confidence: 99%